Twelve-Wavelength-Switchable Thulium-Doped Fiber Laser With a Multimode Fiber Bragg Grating - Qi Qin (IEEE Photonics Journal, 2021)
In this article, a precisely controlled, switchable thulium-doped fiber laser (TDFL) with high optical signal-to-noise ratio (OSNR) is proposed and demonstrated. A home-made multimode fiber Bragg grating (MMFBG) with multireflection peaks was used as an optical filter to select the desired lasing channel. Using a manually controlled fusion splicer, the axial misalignment was applied between the single mode fiber and the MMFBG to switch the output wavelength. In the experiment, the number of switchable lasing lines was up to 12, and the fluctuation of the center wavelength and output power was less than 0.03 nm and 0.67 dB, respectively. A maximum slope efficiency of 1.3% was obtained when the axial misalignment was 0 μm, and the OSNR was higher than 65 dB. In addition, the proposed fiber laser was used as an optical fiber laser sensor to quantify the strain applied on the MMFBG, and a sensitivity of 1.16 pm/μϵ was obtained.